2000
DOI: 10.1111/1467-8624.00150
|View full text |Cite
|
Sign up to set email alerts
|

Early Maternal and Child Influences on Children's Later Independent Cognitive and Social Functioning

Abstract: The present study examined whether parenting and child characteristics of 2- and 3 1/2-year-old children had common paths of influence on their 4 1/2-year independent cognitive and social functioning. Structural equation modeling was guided by hypotheses that assumed children's later independence is facilitated by specialized parental support in early social interactions. To address the importance of variability in early development for understanding children's later independence, we included 104 term and 185 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
280
1
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(321 citation statements)
references
References 72 publications
24
280
1
13
Order By: Relevance
“…Other studies drew attention to the importance and influence of perinatal risk factors (medical complications during birth, hypoxia, hypertension, white matter abnormalities) in preterm children, particularly regarding their cognitive and language development (17,41,46,69). Similarly, the influence of contextual risk factors (socioeconomic status, educational level and parental interactive style, mother-child attachment and type of attachment, parental and maternal emotional adjustment and mental health, negative maternal anxiety and displayed affect, support networks, early parenthood, expectations and characteristics of the proposed task) on the cognitive, communicative-linguistic, and especially emotional development, of preterm children has also been highlighted (17,39,45,49,66,68,69,71,72,74,75). The majority of these studies investigated the influence of sociocultural factors as covariables on the psychological development of preterm children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies drew attention to the importance and influence of perinatal risk factors (medical complications during birth, hypoxia, hypertension, white matter abnormalities) in preterm children, particularly regarding their cognitive and language development (17,41,46,69). Similarly, the influence of contextual risk factors (socioeconomic status, educational level and parental interactive style, mother-child attachment and type of attachment, parental and maternal emotional adjustment and mental health, negative maternal anxiety and displayed affect, support networks, early parenthood, expectations and characteristics of the proposed task) on the cognitive, communicative-linguistic, and especially emotional development, of preterm children has also been highlighted (17,39,45,49,66,68,69,71,72,74,75). The majority of these studies investigated the influence of sociocultural factors as covariables on the psychological development of preterm children.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies compared the cognitive component and social-emotional aspects (35,36,37,44,48,49,73,75) and yet others compared communicative-linguistic skills and emotional development (48,74). However, no studies were found that investigated the influence of prematurity on all the developmental domains at the same time, in the same research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os efeitos da diretividade materna no desenvolvimento da criança nascida prematura foram estudados por Landry, Smith, Swank e Miller-Loncar (2000), os quais demonstraram que estes variam de acordo com a idade da criança. A diretividade materna aos dois anos influenciou positivamente as habilidades cognitivas e sociais da criança aos 3 anos e 6 meses, enquanto a diretividade aos 3 anos e seis meses influenciou direta e negativamente a independência social e cognitiva da criança aos 4 anos e 6 meses.…”
Section: Efeitos Da Interação Mãe-criança Nascida Pré-termo No Desenvunclassified
“…relationship between mothers and their infants). The available researches focused heavily on this Dyadic Relationship (Landry et al, 2000), as a central relationship in learning self-regulations, this includes attention regulation and future cognitive efficiency. The theoretical cultural and social view, refers to the value of studying child interaction with his caregiver.…”
Section: Introductionmentioning
confidence: 99%